The elementary school after Fujimori - Miyashiro Salas, Hiroshi Jesús (2020)
This article is based, first, on the author’s experience in the second bimester of the sixth grade of primary school in the 2000. And second, theoretical and documentary information on the thesis entitled From Restoration to Persecution: Formation of Nikkei Identity in Peru. This article is ordered as follows: 1) The stereotype, where an introduction and summary of the history of the stereotype in which the descendants of Japanese are fitted, using the information of the mentioned thesis and, 2) The primary after Fujimori, where the author’s experiences are developed in the sixth grade of primary school, to finish with the conclusions.